Challenges in Dengue Fever in the Elderly: Atypical Presentation and Risk of Severe Dengue and Hospita-Acquired Infection - Rowe, Emily K. (Public Library of Science, 2014)
BACKGROUND/METHODS: To better understand dengue fever in the elderly, we compared clinical features, World Health Organization (WHO) dengue classification and outcomes between adult (<60) and elderly (≥60) dengue patients. We explored the impact of co-morbidity and hospital-acquired infection (HAI) on clinical outcomes in the elderly. All patients managed at the Communicable Disease Centre, Singapore, between 2005 and 2008 with positive dengue polymerase chain reaction (PCR) or who fulfilled WHO 1997 or 2009 probable dengue criteria with positive dengue IgM were included. RESULTS: Of the 6989 cases, 295 (4.4%) were elderly. PCR was positive in 29%. The elderly suffered more severe disease with more dengue haemorrhagic fever (DHF) (29.2% vs. 21.4%) and severe dengue (SD) (20.3% vs. 14.6%) (p<0.05). Classic dengue symptoms were more common in the adult group. The elderly were less likely to fulfill WHO 1997 (93.6% vs. 96.4%) (p = 0.014), but not WHO 2009 probable dengue (75.3% vs. 71.5%). Time to dengue diagnosis was similar. There was no significant difference in the frequency of warning signs between the two groups, but the elderly were more likely to have hepatomegaly (p = 0.006) and malaise/lethargy (p = 0.033) while the adults had significantly more mucosal bleeding (p<0.001). Intensive care admission occurred in 15 and death in three, with no age difference. Notably, the elderly stayed in hospital longer (median 5 vs. 4 days), and suffered more pneumonia (3.8% vs. 0.7%) and urinary infection (1.9% vs. 0.3%) (p = 0.003). Predictors of excess length of stay were age (adjusted odds ratio [aOR] 2.01, 95% confidence interval [CI] 1.37–2.88), critical illness (aOR 5.13, 95%CI 2.59–9.75), HAI (aOR 12.06, 95%CI 7.39–19.9), Charlson score (aOR 6.9, 95%CI 2.02–22.56) and severe dengue (DHF/dengue shock syndrome/SD) (aOR 2.24, 95%CI 1.83–2.74). CONCLUSION: Elderly dengue patients present atypically and are at higher risk of DHF, SD and HAI. Aside from dengue severity, age, co-morbidity and HAI were associated with longer hospital stay.